Organizational Effectiveness and Green Human Resources Management - Mardikaningsih, Rahayu (Bulletin of Science, Technology and Society, 2024)
This research analyzes the effectiveness of organizations in implementing Green Human Resource Management (GHRM), focusing on sustainable practices and their implications for organizational performance. The findings indicate that GHRM encompasses environmentally conscious approaches to recruitment and selection, training, performance management, compensation, and the cultivation of an organizational culture that supports sustainability. Implementing GHRM has been shown to enhance employee productivity, economic performance, corporate image, and long-term viability. The study highlights the critical role of GHRM in fostering a sustainable organizational culture, strengthening employee engagement, promoting team cohesion, and improving company reputation. Further research is recommended to explore the relationship between GHRM and organizational effectiveness through cross-disciplinary perspectives and broader empirical data. In conclusion, GHRM is not only a reflection of corporate social responsibility but also a strategic approach to gaining competitive advantage and ensuring long-term success in the face of global environmental challenges.